Aspectos sobre travestilidade e envelhecimento: história, corpo e imigração - Mountian, Ilana (Quaderns de Psicologia, 2015)
This article brings some aspects on travestility and transsexuality and ageing, based on the research Travestility and Ageing. There is a lack of research on the theme of ageing of the travesti and transsexual population, while there are a large number of aspects that need visibility and further debate. Considering the transphobic context, some aspects are highlighted, such as, health of travesties and transsexual people considering the body modifications; immigration; and the history told by them. In this sense, it is pointed out the importance of giving voice to travesties and transgender population, since aspects related to the effects of transphobia are continuously ignored and obscured, which brings to the fore the question of guarantee of human rights to travesties and transgender people, while it also reveals how these groups are configured in history.